Measuring the Level Scientific Argumentation Ability of Biology Prospective Teacher - Firdaus, Laras; Royani, Ida (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2022)
This research is a descriptive study conducted at the Mandalika University of Education which aims to measure the level of scientific argumentation ability of biology prospective teacher at the Mandalika University of Education. A total of 20 respondents were involved in this study. The instrument used to measure the level of scientific argumentation ability is an open-ended question consist of 3 items. The data obtained were then analyzed descriptively. As a result and conclusion, that the level of scientific argumentation ability of biology prospective teacher is still low. Therefore, learning methods are needed that can help students to improve their scientific argumentation ability. There are several ways that can be taken to improve the scientific argumentation ability of biology prospective teacher. One of them is by using Socio-Scientific Issues (SSI). For further research using SSI, it must be done with good planning, preparing controversial themes or topics that will become a matter of debate during the learning process.